МОДЕРНІЗМ В УКРАЇНСЬКІЙ КУЛЬТУРІ КІНЦЯ ХІХ ст. – ПОЧАТКУ XX ст. - Фільова, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
У статті аналізується модернізм в українській культурі кінця ХІХ ст. − початку ХХ ст. Розглядається поняття «модернізм» з позиції культурології. Аналізуються передумови появи модернізму в культурі. Виділяються особливості українського модернізму. З’ясовується роль модернізму в розвитку української культури. Ключові слова: модернізм, українська культура, новаторська культура. Филёва Т. В. Модернизм в украинской культуре конца ХІХ ст. – начала ХХ ст. В статье анализируется модернизм в украинской культуре конца ХІХ ст. – начала ХХ ст. Рассматривается понятие «модернизм» с позиции культурологии. Анализируются предпосылки появления модернизма в культуре. Выделяются особенности украинского модернизма. Определяется роль модернизма у развитии украинской культуры. Ключевые слова: модернизм, украинская культура, новаторская культура. Fileva T. V. Modernism in the culture of Ukrainian end XIX - the beginning of XX century. This paper presents and analyses the modernism in the culture of Ukrainian end XIX – the beginning of XX century. Concepts of «modernism» with position of culturology are considered. Preconditions of appearance modernism in the culture are analyzed. Peculiarities modernisms of Ukrainian are emphasized. Role of modernism in the development culture of Ukrainian are defined. Key words: modernism, culture of Ukrainian, innovation culture.